Codage phonologique et boucle articulatoire en mémoire de travail - Michel Billières (Corela)
From the outset Franch as a Foreign Language textbooks for beginners offer reeading activities. A lot of the research in psycholinguistic shows that the process articulatory loop is activated within the working memory while reading. The Foreign reader uses their mother tongue sounds because is a victim of the phonological deafness phenomenum. Once again, the importance of the phonetic correction during the early stages of language learning is questioned. The article presents the sounds that the student uses when he reads. Working on the phonetic correction orally will improve sound recognition garanteeing an improved phonetic code that in turn will have positiveconsequences on the reading activity.